HUBUNGAN ANTARA LAMA AKTIVITAS PERKULIAHAN DENGAN TEKANAN DARAH PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA TAHUN 2022 - I GUSTI NGURAH ADI DWIVA RADITYA, (2023)
The high prevalence of prehypertension and hypertension in adolescence due to duration of campus activities was a concern because long working hours have been associated with increased blood pressure, however several studies have shown inconsistent results. This study aims to determine the correlation between the duration of campus activities and blood pressure in students of the Faculty of Medicine at UPNVJ. This research was a cross sectional study with the method of analytical survey. The independent variable was measured using self-administered questionnaire, Perceived Stress Scale (PSS), Global Physical Activity Questionnaire (GPAQ), Pittsburgh Sleep Quality Index (PSQI). While for blood pressure, a physical examination was carried out using a digital tensimeter. The sample in this study were 48 respondents and was chosen using simple random sampling. Bivariate analysis was using an alternative chi-square test that is Fisher's test. The results showed that the duration of campus activity [p = 0.176; OR = 0.357 (95% CI, 0.09-1.36)], stress level [p = 0.870; OR = 0.826 (95% CI, 0.24-2.77)], physical activity [p = 0.694; OR = 1.587 (95% CI, 0.62-3.98)], and sleep quality [p = 0.345; OR = 0.375 (95% CI, 0.07-1.99)] has p-value > 0.05. Meaning that there is no significant relationship between the duration of campus activity with blood pressure in students of the Faculty of Medicine at UPNVJ. For further research, it is suggested to add more independent variable such as sodium intakes and use different method with Cohort.